MODE I MICRO CRACK PROPAGATION SIMULATION IN TWO-DIMENSIONAL MATERIAL - Ikhsan, Armanda
In this thesis we made uniaxial tension model for silicene. We use the molecular dynamic method to made this model. Because of silicene have low-buckled honeycomb structure, so the model we created is three-dimensional (3D) model. But to make it easy to observe, we still generate the result in two dimensions (2D).We use a spring to model the bond between silicene atoms based on Hooke’s law. For uniaxial tension test, we fixed a left boundary of the model, loading force on the right boundary of the model, and free at the upper and lower boundary of the model. We validate our program by make two comparison with Comsol and experiment. At the last, we will show some results from our simulations.